anonymous
  • anonymous
Solve. x2 - 10x = -21
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
mathstudent55
  • mathstudent55
First, add 21 to both sides. Once you have all three terms on left side equaling zero on right side, try to factor the left side. Then set each factor equal to zero and solve both equations. If you can't factor it, the use the quadratic formula.
anonymous
  • anonymous
Simplifying x2 + -10x = -21 Reorder the terms: -10x + x2 = -21 Solving -10x + x2 = -21 Solving for variable 'x'. Reorder the terms: 21 + -10x + x2 = -21 + 21 Combine like terms: -21 + 21 = 0 21 + -10x + x2 = 0 Factor a trinomial. (3 + -1x)(7 + -1x) = 0 Subproblem 1Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Subproblem 2Set the factor '(7 + -1x)' equal to zero and attempt to solve: Simplifying 7 + -1x = 0 Solving 7 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1x = 0 + -7 -1x = 0 + -7 Combine like terms: 0 + -7 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7Solutionx = {3, 7}
anonymous
  • anonymous
oh wow thank you!

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Np :)
mathstudent55
  • mathstudent55
x^2 - 10x = -21 Add 21 to both sides: x^2 - 10x + 21 = 0 Factor left side: (x - 7)(x - 3) = 0 Set each factor equal to zero and solve: x - 7 = 0 or x - 3 = 0 x = 7 or x = 3

Looking for something else?

Not the answer you are looking for? Search for more explanations.